Variations of Soybean Meal and Corn Mixed Substrates in Physicochemical Characteristics and Microbiota During Two-Stage Solid-State Fermentation - Su, Weifa; Jiang, Zipeng; Hao, Lihong; Li, Wentao; Gong, Tao; Zhang, Yu; Du, Shuai; Wang, Cheng; Lu, Zeqing; Jin, Mingliang; Wang, Yizhen (Frontiers in Microbiology, 2021)
Corn germ meal (CGM) and corn gluten feed (CGF) are the two main corn byproducts (CBs) obtained from corn starch extraction. Due to their high fiber content, low protein content, and severe imbalance of amino acid, CBs are unable to be fully utilized by animals. In this study, the effect of microorganism, proteases, temperature, solid–liquid ratio, and time on nutritional properties of CB mixture feed (CMF) was investigated with the single-factor method and the response surface method to improve the nutritional quality and utilization of CBs. Fermentation with Pichia kudriavzevii, Lactobacillus plantarum, and neutral protease notably improved the nutritional properties of CMF under the fermentation conditions of 37°C, solid–liquid ratio (1.2:1 g/ml), and 72 h. After two-stage solid-stage fermentation, the crude protein (CP) and trichloroacetic acid-soluble protein (TCA-SP) in fermented CMF (FCMF) were increased (p < 0.05) by 14.28% and 25.53%, respectively. The in vitro digestibility of CP and total amino acids of FCMF were significantly improved to 78.53% and 74.94%, respectively. In addition, fermentation degraded fiber and provided more organic acids in the CMF. Multiple physicochemical analyses combined with high-throughput sequencing were performed to reveal the dynamic changes that occur during a two-stage solid-state fermentation process. Generally, Ascomycota became the predominant members of the community of the first-stage of fermentation, and after 36 h of anaerobic fermentation, Paenibacillus spp., Pantoea spp., and Lactobacillales were predominant. All of these processes increased the bacterial abundance and lactic acid content (p < 0.00). Our results suggest that two-stage solid-state fermentation with Pichia kudriavzevii, Lactobacillus plantarum, and protease can efficiently improve protein quality and nutrient utilization of CMF.